2016
DOI: 10.1080/2162402x.2016.1232220
|View full text |Cite
|
Sign up to set email alerts
|

Targeting B-cell malignancies through human B-cell receptor specific CD4+T cells

Abstract: The B-cell receptor (BCR) expressed by a clonal B cell tumor is a tumor specific antigen (idiotype). However, the T-cell epitopes within human BCRs which stimulate protective immunity still lack detailed characterization. In this study, we identified 17 BCR peptide-specific CD4 C T-cell epitopes derived from BCR heavy and light chain variable region sequences. Detailed analysis revealed these CD4 C T-cell epitopes stimulated normal donors' and patients' Th1 CD4C T cells to directly recognize the autologous tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Idiotype-specific CD4 + T cells able to selectively lyse tumor cells have been isolated from peripheral blood of patients across different B cell malignancies (110). Khodadoust et al demonstrated that MHC II-restricted presentation of neoantigens arising from Ig rearrangement is common in mantle cell lymphoma.…”
Section: Classes Of Neoantigens Not Derived From Somatic Mutationsmentioning
confidence: 99%
“…Idiotype-specific CD4 + T cells able to selectively lyse tumor cells have been isolated from peripheral blood of patients across different B cell malignancies (110). Khodadoust et al demonstrated that MHC II-restricted presentation of neoantigens arising from Ig rearrangement is common in mantle cell lymphoma.…”
Section: Classes Of Neoantigens Not Derived From Somatic Mutationsmentioning
confidence: 99%
“…However, a strong induction of tumor-specific degranulating cytotoxic T cells, specific for either class-I-restricted CD8 or class-II-restricted CD4 idiotype epitopes, was detected in the peripheral blood of the 3 patients exhibiting a complete clinical response, showing a peak generally at 6-9 months after the beginning of the treatment, when objective clinical responses were observed. In this regard, it is worth mentioning that also tumor-specific CD4 þ T cells have recently been reconsidered as important effector cells in the immune control of B-cell lymphomas (34,35) because IGVH-derived neoantigens are most frequently presented by MHC-II (34) Although our preclinical studies (Fig. 1) and previous evidence by us (14)(15)(16)(17) and others, both in preclinical models (36) and patients (5), strongly support a critical role for DC, there is the remote hypothesis that rituximab can be also important for determining clinical and immune response.…”
Section: Discussionmentioning
confidence: 99%